Growth Opportunities, Debt policy, and Firm Value Relationship - subagyo Subagyo (Universitas Sains dan Teknologi Komputer, 2020)
This research aims to investigate the role of growth opportunities in affecting the relationship of debt policy with firm value. I predict growth opportunities as variables that moderate the relationship of debt policy with the firm value. Sample using sub-sector Various Industries 2016-2019 period, Indonesia Stock Exchange (BEI), Using purposive sampling techniques got 171 samples separated in 93 samples of corporate growth and 78 corporate, not growth. The findings of this study 1) Sales growth is suitable as a proxy for growth opportunities. 2) opportunity growth strengthens the relationship between debt policy and firm value. 3) Corporate that does not grow, debt policies can weaken the firm's value